Rainwater propeller pumps structural integrity. Issue 4 (27th June 2019) - Galatanu, Sergiu Valentin; Muntean, Sebastian; Marsavina, Liviu; Ailinei, Iulian Ionut; Micota, Dan
Abstract : Purpose: The purpose of this paper is to focus on the structural integrity of the rainwater propeller pumps installed in the municipal wastewater treatment plant (WTP). Design/methodology/approach: A numerical analysis is performed to determine the maximum shear stress on the fasten bolts. The rainwater propeller pump is examined in operation at normal conditions and when one blade is progressively blocked. Findings: The failure mechanism of the rainwater pump impeller is determined. Research limitations/implications: The fibbers and wastes are discharged together with rainwater during storms with these types of pumps to avoid the flood of the WTP. Several catastrophic events have occurred in service due to the fibbers clog the gap between the impeller blades and the pump casing. The clogging process is partially understood so actual technical solutions deal with effects rather the main causes. Practical implications: The operation time of all seven rainwater pumps installed in Timisoara's WTP is investigated. Climate changes in Banat region and new waste properties found in the wastewater require appropriate technical solutions. A technical solution is proposed based on these investigations to extend the operation time and to diminish the operation and maintenance costs. Social implications: These large pumps are installed in the urban sewage centralised system implemented in the most cities. The access to the sewerage network is a requirement of any community, regardless of the social status. Originality/value: The fracture surfaces of both fastening bolts of the rainwater pump impellers produced in service are examined. As a result, it has been identified that the catastrophic events are due to the brittle fracture of both fasten bolts between the impeller blades and the pump hub, respectively. The catastrophic events of the rainwater propeller pumps are directly correlated to the clog level of the impeller. The numerical simulation is performed to determine the maximum shear stress on the fasten bolts. The case with pump operating at normal conditions is performed identifying its vulnerabilities to clog conditions. Next, one impeller blade is progressively blocked considering three time stop scenarios associated with different clog levels. Conclusively, the operating time of the rainwater pump up to the catastrophic failure is correlated to the clog level of the impeller.